Analisis Metode dan Pendekatan dalam Manajemen Proyek pada Dunia Pendidikan - Budi Suhartono; Budi Budi; Amiruddin Siahaan; Inom Nasution; makmur syukri (Edumaspul: Jurnal Pendidikan, 2022)
This study seeks to examine the project management approach and the application of project management in education. In this study using the method of library research (library research). In obtaining research data, researchers collect, analyze, organize, sources from articles, books, previous research on methods and approaches in project management. The results of the research are (1) Project Management is a discipline that must be possessed by every professional individual in an organization because the dynamics of an ever-changing organization requires an organization or must be able to create ideas that are embodied in projects. Projects are complex business activities. , are not routine in nature, have limited time, budget and resources and have special specifications for the products to be produced. (2) The Project Management Method used is CPM (Critical Path Method). 1) critical method (CPM) and linear programming approach (Linear Programming), 2) critical method is basically a time-activated scheduling method. The purpose of the critical method is to establish the relationship between time and cost by reducing the target time and considering operational costs. (3) Waterfall Project Management Approach, Critical Path Method, Critical Chain Project Management (CCPM).